2003
DOI: 10.1074/jbc.m209980200
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity-induced Aquaporin-1 (AQP1) Expression Is Mediated by the Activation of MAPK Pathways and Hypertonicity-responsive Element in the AQP1 Gene

Abstract: Aquaporin-1 (AQP1) is a water channel that is induced by hypertonicity. The present study was undertaken to clarify the osmoregulation mechanism of AQP1 in renal medullary cells. In cultured mouse medullary (mIMCD-3) cells, AQP1 expression was significantly induced by hypertonic treatment with impermeable solutes, whereas urea had no effect on AQP1 expression. This result indicates the requirement of a hypertonic gradient. Hypertonicity activated ERK, p38 kinase, and JNK in mIMCD-3 cells. Furthermore, all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
128
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 39 publications
(39 reference statements)
13
128
1
Order By: Relevance
“…Similar to results of the present study, p38, ERK1/2, and JNK MAPK activation by hypertonicity has been demonstrated in inner medullary collecting duct cells and in cells of the medullary thick ascending limb of Henle's loop (43)(44)(45). A role of p38, ERK and JNK in the transcriptional regulation of various aquaporins by hypertonicity has been shown in renal and lung epithelial cells and in astrocytes (45)(46)(47). Data from our present study indicate that MAPKs additionally participate in the accumulation of AQP2 at the plasma membrane, but not at the TGN, in renal CD principal cells immediately following hypertonic challenge.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to results of the present study, p38, ERK1/2, and JNK MAPK activation by hypertonicity has been demonstrated in inner medullary collecting duct cells and in cells of the medullary thick ascending limb of Henle's loop (43)(44)(45). A role of p38, ERK and JNK in the transcriptional regulation of various aquaporins by hypertonicity has been shown in renal and lung epithelial cells and in astrocytes (45)(46)(47). Data from our present study indicate that MAPKs additionally participate in the accumulation of AQP2 at the plasma membrane, but not at the TGN, in renal CD principal cells immediately following hypertonic challenge.…”
Section: Discussionsupporting
confidence: 91%
“…AQP1 is the most abundant isoform in the peritoneum, and the only one that has been consistently located in the capillary endothelium. It must be noted that the expression of AQP1 in mesothelial, endothelial and epithelial cells may be induced by exposure to osmotic agents in vitro, reflecting the presence of hypertonicity response elements in the promoter (27,28). Because the mesothelium does not represent a significant functional barrier for water transport in PD, the functional importance of water channels at that level remains unclear.…”
Section: Aquaporin-1 Is the Ultrasmall Pore Of The Peritoneal Membranementioning
confidence: 99%
“…In addition to up-regulation of organic osmolyte transporters, hypertonicity induces expression of aquaporin (AQP) waterchannel proteins (15)(16)(17). Aquaporins are the primary determinants of osmotic gradient-dependent rapid water movement in or out of cells (18).…”
mentioning
confidence: 99%
“…Aquaporins are the primary determinants of osmotic gradient-dependent rapid water movement in or out of cells (18). Hypertonic induction of AQP5, a waterchannel protein expressed in lung and several secretory epithelia (16), and AQP1, which is expressed at multiple sites including lung and kidney (16,17), require activation of mitogen-activated protein kinase (MAPK) signaling cascades, which are known to participate in osmotic signaling in yeast and mammals (19). MAPK activation often follows the activation of G proteincoupled receptors (GPCRs) and͞or receptor tyrosine kinases (RTKs), e.g., the epidermal growth factor receptor (EGFR) or human epidermal growth factor receptor (HER).…”
mentioning
confidence: 99%